2016
DOI: 10.1001/jamaoncol.2015.4437
|View full text |Cite
|
Sign up to set email alerts
|

Identification ofBRAFKinase Domain Duplications Across Multiple Tumor Types and Response to RAF Inhibitor Therapy

Abstract: The Raf family (ARAF, BRAF, CRAF) of serine/threonine kinases are activators of downstream MEK kinases in the Ras-Raf-MEK-ERK signaling pathway. BRAF is the most potent activator of MEK kinases, and alterations in the Ras-Raf-MEK-ERK pathway are observed in nearly 30% of human malignant neoplasms. More than 300 BRAF mutations are described, mostly within exons 11 through 15 of the catalytic kinase domain (CR3), and BRAF V600E accounts for 90% of observed BRAF mutations. 1 Alternate mechanisms of BRAF activatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 6 publications
1
13
0
Order By: Relevance
“…In fact, BRAF‐KDDs have also been reported in gliomas . More recently, the analysis of 50,000 samples spanning multiple tumor types found that BRAF‐KDDs comprised 0.5% of all BRAF alterations identified . Additionally, KDD events were identified in other genes, including MET, FGFR1, FGFR3, RET, ERBB2, ALK , and NTRK in different types of tumors as potential driver mutations .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, BRAF‐KDDs have also been reported in gliomas . More recently, the analysis of 50,000 samples spanning multiple tumor types found that BRAF‐KDDs comprised 0.5% of all BRAF alterations identified . Additionally, KDD events were identified in other genes, including MET, FGFR1, FGFR3, RET, ERBB2, ALK , and NTRK in different types of tumors as potential driver mutations .…”
Section: Discussionmentioning
confidence: 99%
“…14 More recently, the analysis of 50,000 samples spanning multiple tumor types found that BRAF-KDDs comprised 0.5% of all BRAF alterations identified. 15 Additionally, KDD events were identified in other genes, including MET, FGFR1, FGFR3, RET, ERBB2, ALK, and NTRK in different types of tumors as potential driver mutations. 16 It is therefore important to increase the panel coverage of intronic regions of such kinases for comprehensive NGS analyses in the future.…”
Section: Discussionmentioning
confidence: 99%
“…This study identified other noteworthy genomic targets in a wide range of SGCs. For instance, though BRAF mutations were not common in this study, they did tend to be activating and one AciCC patient with a BRAF gene fusion responded to a multikinase inhibitor targeting BRAF [ 21 ]. The BRAF GA rate in this study (2.7%) was similar to the 2% observed in COSMIC, though the rate reported here is a little lower than that reported in another SDC study [ 12 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…We also found that EGFR -KDD occurred in other types of human tumors, including gliomas, sarcoma and Wilms’ tumor [ 143 ]. BRAF -KDD has been reported in gliomas and advanced acinic cell tumor [ 144 , 145 ]. BRAF is an intracellular serine/threonine kinase; however, we discuss here as demonstration of principle.…”
Section: Oncogenic Activation Of Receptor Tyrosine Kinasesmentioning
confidence: 99%